Kombucha: um estudo exploratório do perfil químico e das propriedades antifúngicas - Mazuchi, Natalia Seron Brizzotti (2023)
Introduction: Kombucha is a drink that originated in Manchuria, obtained by fermenting tea (Camellia sinensis) and sugar by a “symbiotic culture of bacteria and yeast” (SCOBY). This drink has several beneficial effects, including antimicrobial activity. Due to the importance and prevalence of fungal infections, whose etiology is variable in species and susceptibility profiles to antifungals, the discovery of new antifungal molecules is crucial. Objective: This study aimed to evaluate the antifungal activity of Kombucha extracts against common dermatophytosis agents and the combined effect of fluconazole. Material and Methods: Camellia sinensis black, green and white tea was prepared as a base for developing 20 g of SCOBY (Symbiotic Culture of Bacteria and Yeast) followed by incubation for 10, 20 or 30 days, considering the tea fermentation times. Afterward, the teas were filtered through a membrane system. The extracts were obtained by liquid-liquid extraction with ethyl acetate and dried in a rotary evaporator. The chromatographic profiles were determined by high-performance liquid chromatography (HPLC) and toxicity tests were conducted on the Galleria mellonella model. The broth microdilution minimum inhibitory concentration (MIC) of the extracts was determined against clinical isolates and standard strains (ATCC) of Trichophyton rubrum, Trichophyton mentagrophytes, Epidermophyton flocosum and Microsporum canis. The combined antimicrobial response between Kombucha extracts and fluconazole was investigated using checkerboard assays. Results: The chromatographic profiles demonstrated the presence of different components, but no correlation could be made with the MIC values xi found. The CB for all fermentation times showed toxicity killing more than 50% of the larvae in five days of incubation. Assays with T. rubrum and T. mentagrophytes showed MIC values between 62.5 and 2,000 μg/mL. Green tea and Kombucha showed the best MIC results after 10-day fermentation. Kombucha extract with black tea, tested against clinical isolates T. rubrum, T. mentagrophytes, E. flocosum and M. canis, showed MIC values between 31.25 and 500 μg/mL. There was a synergistic action between Kombucha extract in black tea and fluconazole for T. rubrum, T. mentagrophytes and E. flocosum fungi. However, against the M. canis species, the action was addictive. Conclusion: Kombucha extracts may be a viable alternative for developing new treatment strategies for dermatophytosis since the antimicrobial response was adequate.